Perbaikan Teknologi Pakan untuk Menjaga Keutuhan Kelompok Tani Penerima Bantuan Ternak Sapi di Kabupaten Tanah Datar dan Kota Payakumbuh, Sumatera Barat - . Khalil; . Reswati; Yulianti Fitri Kurnia; . Ferawati (Institut Pertanian Bogor, 2017)
The integrity of beneficiary farmers' groups of Bungo Lapai in the district of Tanah Datar and Tapian Agam in the Payakumbuh City was threatened by the insufficient capability of the groups to fulfill forage requirement and low reproductive performances of their cattle. The aims of the present community services were to maintain the integrity of the two beneficiary groups of cattle farmer through extension program and technical skill training for improvement of technology and nutritive values of forages. The program was initiated by the motivation of the group members through extension program in good farming practices. The groups were then offered feed handling and process facilities, followed by training programs on the techniques of collecting and preserving large amount green feed in the form of silage. The group members were also provided the technical skills to improve the nutritional value of forage through the preparation of supplemented feed produced by utilizing locally available materials that are easily obtained by the farmer. The overall achievements of the program included better motivation of group members in applying good farming practices. Improvement of technical skills in the preservation of large quantity of green fodder in form of silage gave a positive impact of has a good impact on farmer motivation. The use mineral feed supplements might improve the nutritional value of forages and reproductive performances of cattle.